Implementasi Kebijakan Hak Guna Bangunan Di Kantor Wilayah Badan Pertanahan Nasional Provinsi Bengkulu - Diana Puspita; Evi Lorita; Maryaningsih Maryaningsih (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This research aims to understand the implementation of the Building Use Rights (HGB) policy at the Regional Office of the National Land Agency in Bengkulu Province. The study uses a qualitative descriptive method with data collection through observation, interviews, documentation, and literature review. The informants consist of five individuals, including three key informants and two main informants. The findings reveal that the implementation of HGB policy based on Government Regulation No. 18 of 2021 is carried out through ten main indicators: granting HGB, duration and extension, transfer of rights, legal protection, land utilization, administrative simplification, certification and legal certainty, infrastructure support, administrative sanctions, and governance and supervision. Although implementation is ongoing, improvements are needed in public understanding and inter-agency coordination.